Uncovering negative sentiments: a study of indonesian twitter users' health opinions on coffee consumption - Budiarto, Laksono; Rokhman, Nissa Mawada; Uriu, Wako (Association for Scientific Computing Electrical and Engineering, 2023)
The increase in coffee consumption among the public is due to several reasons, including health and lifestyle reasons. Awareness of the positive and negative effects of coffee consumption has also increased in society. This research is a sentiment analysis that aims to investigate Twitter users' opinions about the impact of coffee consumption on their health. The method used involves data collection using the RapidMiner application, utilizing the Twitter Application Programming Interface (API) function connected to a prepared Twitter account. The obtained data underwent data cleaning, saved as an Excel file type, training and testing, and model evaluation. Then, the data was classified into three categories: Negative Opinion, Neutral Opinion, and Positive Opinion. The results showed that less than 10% of opinions were positive, 19% were neutral, and 73% were negative. The opinions obtained are useful information for stakeholders in the coffee industry. They can also be used to determine better steps in educating the public about coffee.